HIV Status and Psychological Resilience among Tuberculosis Patients in VCT Services in Gorontalo City, Indonesia: A Cross-Sectional Study - Irwan; Deliyana I. Katili; Mar’atuljannah Una; Tantri R. Popalo (The Open Public Health Journal, 2026)
Introduction HIV/AIDS and Tuberculosis (TB) cases in Indonesia, including Gorontalo City, have shown a continued increase and present multifaceted health challenges that extend beyond medical issues to psychological aspects. TB patients living with HIV are particularly vulnerable to mental distress due to long-term illness and persistent social stigma. In this context, resilience plays an important role in supporting treatment adherence and overall well-being. Methods An analytical survey with a cross-sectional design was employed, involving 70 respondents. Respondents were recruited using a total sampling technique. Data were collected using structured questionnaires and analyzed using the Chi-Square test. The analysis revealed a statistically significant relationship between HIV/AIDS status and resilience levels ( p = 0.025). Results Interestingly, the findings indicate that TB patients with HIV-positive status tend to demonstrate higher levels of resilience compared to those who are HIV-negative, suggesting the presence of adaptive psychological mechanisms developed through prolonged engagement with healthcare services. The analysis revealed a statistically significant relationship between HIV/AIDS status and resilience levels ( p = 0.025). Discussion These findings suggest that HIV-positive TB patients may benefit from stronger psychosocial support systems, including counseling and continuous interaction with health workers during the VCT process. Conclusion TB patients with HIV-positive status appear to exhibit better psychological adaptability and resilience, which may be influenced by family support, healthcare assistance, and counseling services. Therefore, VCT programs should be strengthened not only in terms of clinical care but also through comprehensive psychosocial interventions aimed at enhancing patient resilience.